(untitled) (Research, Society and Development, 2021)
Objective: Describe the prevalence and epidemiological profile of the co-infection of tuberculosis and the HIV virus in the state of Tocantins. Method: Descriptive epidemiological study of new tuberculosis cases coinfected with HIV registered from 2001 to 2020 in Tocantins. Data were collected from the Information Technology Department of the Unified Health System (DATASUS) and tabulated into graphs and tables. Results: There were 199 new cases of TB coinfected with HIV, prevalence of 5%. There was an increase in the co-infection of tuberculosis and HIV from 2.75% in 2001 to 8.90% in 2020. Male cases predominated (76.39%), young adults (50.80%), browns (68.87 %) and predominance in the Capim Dourado health region (36.20%). The extrapulmonary clinical form represented 34.17%. The percentage of cure was only 45.22%. Conclusion: The increase in HIV-coinfected tuberculosis cases, the severity of cases in the extrapulmonary clinical form, the low percentage of cures and the high mortality rate represent the challenges that control programs need to overcome for the clinical management of HIV-associated tuberculosis. The main challenge includes the integration of effective tuberculosis treatment associated with the use of antiretroviral therapy for the prevention of HIV-related comorbidities.